1999
DOI: 10.1080/08035259950169305
|View full text |Cite
|
Sign up to set email alerts
|

Clinically symptomatic central venous catheter-related deep venous thrombosis in newborns

Abstract: The objective of this study was to evaluate the incidence of clinically symptomatic central venous catheter (CVC)-related deep venous thrombosis (DVT) in newborns and small infants and to try to identify clinical and genetic risk factors for catheter-related DVT among children with thrombotic complications. CVC was inserted in 44 consecutive infants (age range 0-90 d) during the period January 1990 to December 1995 in the neonatal intensive care unit (NICU) of Kuopio University Hospital in Kuopio. The symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Indeed, while data from different registries agree on the fact that most of the thrombotic events in children are likely associated with severe underlying diseases and acquired risk factors, particularly the presence of indwelling catheters, controversy exists on whether or not and to which extent congenital prothrombotic disorders contribute to these thrombotic events [1,7,8,9]. For example, while Nowak-Göttl et al [10 ]demonstrated an increased incidence of congenital prothrombotic disorders in catheter-related thrombosis in newborns and children, in the studies by Manco-Johnson et al [11 ]and Salonvaara et al [12 ]no such association with neonatal catheter-related thrombosis was present. In one study, congenital prothrombotic risk factors have also been shown to contribute to thrombotic complications associated with CVL in children with malignancies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, while data from different registries agree on the fact that most of the thrombotic events in children are likely associated with severe underlying diseases and acquired risk factors, particularly the presence of indwelling catheters, controversy exists on whether or not and to which extent congenital prothrombotic disorders contribute to these thrombotic events [1,7,8,9]. For example, while Nowak-Göttl et al [10 ]demonstrated an increased incidence of congenital prothrombotic disorders in catheter-related thrombosis in newborns and children, in the studies by Manco-Johnson et al [11 ]and Salonvaara et al [12 ]no such association with neonatal catheter-related thrombosis was present. In one study, congenital prothrombotic risk factors have also been shown to contribute to thrombotic complications associated with CVL in children with malignancies [13].…”
Section: Introductionmentioning
confidence: 99%
“…One patient was heterozygous for FVL. 15 One study was performed after 2008. It showed that thrombophilia was present in none of the 13 studied neonates with CVC-related thrombosis.…”
Section: Venous Thrombosis and Thrombophilia In Neonatesmentioning
confidence: 99%
“…Due to the wide variation in reported incidence, it is difficult to ascertain from the existing literature whether the incidence specifically of catheter-related thromboembolism is, in fact, less in neonates than it is in adults. [26][27][28][29] Specifically designed clinical studies would be required to provide a definitive answer to this question.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 However, the incidence of thromboembolic events related to the use of central venous catheters in children is significant although it is not clear whether it is less so than in adults. [26][27][28][29] Recognizing that a number of proteins, such as the contact factors, prothrombin, plasminogen, and a number of inhibitors, are present at low levels in the newborn, and in some cases in children beyond even 6 months of age, it is of interest to determine whether protein adsorption to artificial surfaces is different for infant plasma compared to adult plasma. Such differences are relevant to the prolonged use of central venous catheters in the newborn for nutritional and other purposes.…”
Section: Introductionmentioning
confidence: 99%